1984
DOI: 10.1128/aac.26.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary acute genital herpes in guinea pigs by intraperitoneal administration of fluoropyrimidines

Abstract: evaluated for their efficacies in the treatment of genital infections with herpes simplex virus type 2 in guinea pigs. Intraperitoneal administration of these drugs in daily doses of 100 mg/kg of body weight initiated 24 h after virus inoculation and repeated 2 successive days thereafter inhibited development of genital lesions and reduced shedding of virus without evoking untoward reactions. In a comparative study with this 3-day dosage schedule, the efficacy of dgily doses of 50 mg of FMAU per kg was greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…No evidence for a mutagenic or oncogenic effect was demonstrated. The reported studies in mice and guinea pigs inoculated with HSV-1 or HSV-2 did not show any evidence of toxicity (6,9,13). Our studies in monkeys also showed no evidence of toxicity either grossly or indicated in hematology and clinical chemistry tests performed during the period of treatment.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…No evidence for a mutagenic or oncogenic effect was demonstrated. The reported studies in mice and guinea pigs inoculated with HSV-1 or HSV-2 did not show any evidence of toxicity (6,9,13). Our studies in monkeys also showed no evidence of toxicity either grossly or indicated in hematology and clinical chemistry tests performed during the period of treatment.…”
Section: Resultssupporting
confidence: 54%
“…Guinea pigs inoculated intravaginally with HSV-2 and treated with daily intraperitoneal injections of FIAC, FIAU, or FMAU at 100 mg/kg had reduced mean lesion scores on days 3, 4, 7, and 10 postinfection and a lower titer of virus shed from the vaginal tract on day 4 postinfection (6). FMAU was more effective than either FIAC or FIAU in reducing mean lesion scores when intraperitoneal treatment with the drugs at 50 mg/kg was begun either 24 or 48 h after virus inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…Candidate antiviral drugs that have proven to be effective against HSV-2 infections in animal models and that therefore seem worth pursuing for their potential in the treatment of genital herpes and HSV-2 infections in general include cyclaradine (43) as well as its predecessor vidarabine (34); the 1-(2'-deoxy-2'-fluoro-p-D-arabinofuranosyl)pyrimidine derivatives FMAU, FIAC, and FIAU (27,28); 5-ethyl-2'-deoxyuridine (EDU) (39); phosphonoformate (1,23,24,28); and 9-(1,3-dihydroxy-2-propoxymethyl)guanine (21), particularly when combined with interferon (18)(19)(20). Cyclaradine, vidarabine, and phosphonoformate thereby offer the advan-* Corresponding author.…”
mentioning
confidence: 99%